The role of learning aqidah akhlaq in preventing lying behavior for kindergarten students in Semarang - Safitri, Dhea Ananda; Khunaifi, Agus; Muthohar, Sofa (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Lying tendencies in young children are a prevalent concern that may arise from insufficient cognitive awareness, anxiety over repercussions, or inadequate moral instruction. This study explores how teachings of Aqidah Akhlak can be utilized as a proactive measure against dishonesty in pre-schoolers residing in Semarang City. Employing a qualitative descriptive framework, the research encompasses direct observations, discussions with educators and parents, and an analysis of educational documents. Results indicate that truthfulness can be nurtured effectively through narratives, music, and dramatization that highlight moral teachings. A nurturing educational atmosphere coupled with ongoing cooperation between teachers and families is vital for reinforcing these principles. Nonetheless, the challenge remains in maintaining consistency and distinguishing between creative expressions and lies. This research emphasizes the significance of embedding moral education into everyday classroom interactions to foster honesty from a young age.